Effect of 2-(2-pyridyl)azole-based ancillary ligands (L1-4) on the electrophilicity of the nitrosyl function in [Ru-II(trpy)(L1-4)(NO)](3+) [trpy=2,2 `: 6 `,2 `'-terpyridine]. synthesis, structures, and spectroscopic, electrochemical, and kinetic aspects - Chanda, N.; Paul, D.; Kar, S.; Mobin, Shaikh M.; Datta, Anindya; Puranik, Vedavati G.; Rao, K. K.; Lahiri, Goutam Kumar (Inorganic Chemistry, 2005)
Ruthenium nitrosyl complexes [Ru(trpy)(L1-4)(NO)](3+) (13-16) [trpy = 2,2':6',2"-terpyridine, L-1 = 2-(2-pyridyl)-benzoxazole, L-2 = 2-(2-pyridyl)benzthiazole, L-3 = 2-(2-pyridyl)benzimidazole, L-4 = 1-methyl-2-(2-pyridyl)-1H-benzimidazole] were obtained in a stepwise manner starting from [Ru-II(trpy)(L1-4) (Cl)]ClO4 (1-4) &RARR; [Ru-II(trpy)(L1-4) (H2O)](ClO4)(2) (5-8) &RARR; [Ru-II(trpy)(L1-4) (NO2)ClO4 (9-12) &RARR; [Ru-II(trpy)(L-1,L-2,L-4) (NO)](ClO4)(3) (13, 14, 16)/[Ru-II(trpy)(L-3) (NO)](Cl)(4))(2)(NO3) (15). Crystal structures of 1, 2, 4, 9, 12, 13, 15, and 16 established the stereoretentive nature of the transformation processes. Though the complexes of L1, L3, and L 4 were isolated in the isomeric form A (π-acceptor trpy and azole ring in the equatorial plane and the pyridine and chloride donors in the axial positions), complexes of L 2 preferentially stabilized in form B (trpy and pyridine in the equatorial plane and the azole ring and chloride donors in the axial positions). The v(NO) stretching frequency varied in the range of 1957-1932 cm(-1), 13 &MGT; 14 &MGT; 15 > 16, primarily depending on the electronic aspects of L as well as the isomeric structural forms. The coordinated nitrosyl function underwent successive reductions of [Ru-II-NO+](3+) &RARR; [Ru-II-NO&BULL;](2+) and [Ru-II-NO&BULL;](2+) - [Ru-II-NO-](+), and the first reduction potential follows the order 14 > 13 &MGT; 15 &AP; 16. The nearly axial EPR spectra having nitrogen hyperfine splittings (A &AP; 26 G) at 77 K of 13(-)-16(-) with (g) &AP; 2.0 established that the reduction process is largely centered around the nitrosyl function. Despite an appreciably high v(NO), the complexes were found to be unusually stable even in the aqueous medium. They transformed slowly and only partially into the corresponding nitro derivatives in H2O (k &AP; 10(-4) s(-1) and K = 0.4-3.8). The chloro (1-4), aqua (5-8), and nitro (9-12) derivatives displayed reasonably strong emissions near 700 nm at 77 K (φ = 10(-1)-10(-2)). The aqua derivative 7 was found to interact with the calf thymus and the circular form of p-Bluescript SK DNA.

Effects of conjugation length and donor-acceptor functionalization on the non-linear optical properties of organic push-pull molecules using density functional theory - Datta, Anindya; Pal, S. (Journal of Molecular Structure-Theochem, 2005)
We consider a series of dipolar organic molecules where the donor groups and the acceptor groups are separated by pi-conjugation like phenyl ring or alkene chains. We have performed extensive quantum chemical calculations based on density functional theory (DFT) to calculate their linear and non-linear optical coefficients. We show that though DFT is known to overestimate the polarizabilities of quasilinear systems,the results with proper inclusion of exchange correlation compare well with the experimental studies. On increasing the pi-conjugation length, the coefficients increase non-linearly. We also vary the donor and the acceptor groups and study the role of chemical modifications on the response properties. Herein we suggest experimental methods by which the molecules may be arranged in non-centrosymmetric fashion in the bulk for device integration. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: DFr; donor-acceptor functionalization; non-linear properties; push-pull molecules

Selective recognition of fluoride and acetate by a newly designed ruthenium framework: experimental and theoretical investigations - Kundu, Tanaya; Chowdhury, Abhishek Dutta; De, Dipanwita; Mobin, Shaikh M.; Puranik, Vedavati G.; Datta, Anindya; Lahiri, Goutam Kumar (Dalton Transactions, 2012)
{An effective anion sensor, [Ru-II(bpy)(2)(H2L-)](+) (1(+)), based on a redox and photoactive {Ru-II(bpy)(2)} moiety and a new ligand (H3L = 5-(1H-benzo[d]imidazol-2-yl)-1H-imidazole-4-carboxylic acid), has been developed for selective recognition of fluoride (F-) and acetate (OAc-) ions. Crystal structures of the free ligand, H3L and [1](ClO4) reveal the existence of strong intramolecular and intermolecular hydrogen bonding interactions. The structure of [1](ClO4) shows that the benzimidazole N-H of H2L- is hydrogen bonded with the pendant carboxylate oxygen while the imidazole N-H remains free for possible hydrogen bonding interaction with the anions. The potential anion sensing features of 1(+) have been studied by different experimental and theoretical (DFT) investigations using a wide variety of anions, such as F-, Cl-, Br-, I-, HSO4-, H2PO4-, OAc- and SCN-. Cyclic voltammetry and differential pulse voltammetry established that 1(+) is an excellent electrochemical sensor for the selective recognition kof F- and OAc- anions. 1(+) is also found to be a selective colorimetric sensor for F- or OAc- anions where the MLCT band of the receptor at 498 nm is red shifted to 538 nm in the presence of one equivalent of F- or OAc- with a distinct change in colour from reddish-orange to pink. The binding constant between 1(+) and F- or OAc- has been determined to be logK = 7.61 or 7.88, respectively, based on spectrophotometric titration in CH3CN. The quenching of the emission band of 1(+) at 716 nm (lambda(ex) = 440 nm

Various types of separation membranes - Das, Debasree; Datta, Anindya; Contractor, Aliasgar Qutub (Current Science, 2016)
Membrane-based separation is a superior alternative to conventional processes in many separation problems of practical importance. For maximum effectiveness, both high selectivity and flux are desirable. This article summarizes the global efforts at designing new membrane materials, particularly carbon nanotube (CNT)-based membranes, to achieve the twin objectives mentioned above. Interest in CNT emanates from the excellent transport property of molecules through its frictionless smooth walls, with/without functionalization at the end tips. Permeation of water through graphene oxide (GO) channels, which are otherwise impermeable to solutes, has also generated considerable interest, and GO is being viewed as a promising material for separations. The performances of conducting polymers like polypyrrole, polyaniline, polythiophene-3, 4-ethylenedioxythiophene and their different composites have been studied as a function of changes in morphology and redox behaviour, and this aspect too is covered in the present article. Also, the dependence of the separation performances based on the size, charge and hydrophobic/hydrophilic properties has been discussed in detail. Advances in understanding will have an important bearing on future developments in separation science.
Keywords: carbon nanotube; conducting polymers; flux; graphene oxide; permeability; separation membranes